2003
DOI: 10.1046/j.1423-0410.2003.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

High proficiency in detecting the six major hepatitis C virus genotypes of laboratories involved in testing plasma by nucleic acid amplification technology

Abstract: Since the introduction of mandatory HCV RNA testing of plasma pools for fractionation by nucleic acid amplification technology, we have organised External Quality Assessment studies (EQAs) addressed to blood products manufacturers and blood centres. Here we report the results of a new EQA, the first one to include all six major HCV genotypes. The results, reported by laboratories worldwide, showed that genotypes 1, 2 and 3 were correctly identified in 100% of the tests, genotype 4 in 96.7% and genotypes 5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…However, in case NAT tests are carried out for validation of blood donations, the different nature of the NAT test, screening vs. diagnostic, implies that there should be a dedicated EQAP that takes into account the state of the art of the commercial NAT assays available on the market. In recent years, our EQAPs focused on laboratories that perform NAT tests for screening purposes [6–8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in case NAT tests are carried out for validation of blood donations, the different nature of the NAT test, screening vs. diagnostic, implies that there should be a dedicated EQAP that takes into account the state of the art of the commercial NAT assays available on the market. In recent years, our EQAPs focused on laboratories that perform NAT tests for screening purposes [6–8].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, we gained a good experience in organizing EQAPs for the detection of blood‐borne viruses by NAT addressed to Italian blood transfusion centres (BTCs) [5–9]. In Italy, blood testing for HCV by NAT has been mandatory since June 2002 while NAT for HBV and HIV, originally implemented by transfusion centres on a voluntary basis, became mandatory in April 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Spanish OMCL asked to participate, prompted by the presence, in the panel, of genotype 4, which occurs at a higher prevalence in Spain than in other Western countries [8]. As compared to the EQA/4 [9], this time only genotypes 4 and 5 were represented twice in the panel. In fact, among the six genotypes, 4 and 5 showed the lowest percentages of detection in the previous EQA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous EQA studies found that HCV quantification was dependent upon concentration, with difficulties occurring at the upper and lower limits of detection and that false positives were rare (Schirm et al, 2002;Saldanha, 2001;Mancini et al, 2004). Additionally, a similar study noted that genotype identification varies with genotype from 96.7% to 100% (Gentili et al, 2003). Previous EQA studies for HCV have been limited by low numbers of participants (from 10 to 81), concentrating studies in single countries or Europe only and by presenting data in copies/mL rather than the accepted standardised international units/mL.…”
Section: Introductionmentioning
confidence: 90%
“…Chalker). comparability and parity have improved (Gentili et al, 2003;Schirm et al, 2002;Mancini et al, 2004). Previous EQA studies found that HCV quantification was dependent upon concentration, with difficulties occurring at the upper and lower limits of detection and that false positives were rare (Schirm et al, 2002;Saldanha, 2001;Mancini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%